PENGARUH TAX AVOIDANCE JANGKA PANJANG TERHADAP NILAI PERUSAHAAN DENGAN KARAKTER EKSEKUTIF SEBAGAI VARIABEL PEMODERASI - Ampriyanti, Ni Made; Merkusiwati, Ni Kt Lely Aryani (E-Jurnal Akuntansi, 2016)
The purpose of this study was to determine the effect of long-run tax avoidance on firm’s value with executive character as moderating variables. Research was conducted on Manufacturing Companies listed on the Indonesia Stock Exchange in 2013-2014. Method of sampling was conducted by nonprobability sampling with purposive sampling technique. Data collected through non-participant observation and library method. Data analysis techniques used are moderated regression analysis with 17 firm as a sample. Based on the research results indicate that long-run tax avoidance has negative effect on the firm’s value. This means that long-run tax avoidance can lead to firm’s value has decreased. Executive Character enervated the effect of long-run tax avoidance on firm’s value.
Keywords: Long-Run Tax Avoidance, Executive Character, Firm Value, Manufacturing Company.